Evaluation of an EFL Teacher Training Program in Japan. (March 2018) - Yamada, Mieko
This article presents a study undertaken to evaluate how effectively an English as a Foreign Language (EFL) training program helps Japanese EFL teacher trainees prepare for their future positions. Data were collected via both interviews and surveys. Interviews were first conducted with Japanese teacher trainees enrolled in the program to identify concerns related to their EFL learning and teacher training. Since the interviews revealed potential areas for a new direction in the EFL curricula, surveys were later conducted to focus on the teacher trainees' perceptions of Japan's diversity. This article discusses the findings from interviews and surveys, and offers recommendations for further improvement to the Japanese EFL program.